A Study on the Alternative Solution for Skilled Labour Shortage Issue in Malaysia Construction Industry - Wong, Chee Kai (2020)
Skilled labour shortage have become a serious issues to Malaysia’s construction industry. Which mean the current supply of skilled labour does not meet the entire demand in the construction industry. It lead the Malaysia’s construction industry has the problems to get the sources of skilled labour and had to hire foreign skilled labour to overcome this issues. However, the lack of skilled labour can because by various reason. Hence, the aim of this research is to study the alternative solution for skilled labour shortage in Malaysia’s construction industry. Before get the solution, there must be reasons and impacts when skilled labour shortage occurs. Hence, find out the reason, impact and some current solution though literature review and survey questionnaire. The research method of this project will use quantitative method. All the data will be collected from the respondents and analysis by using SPSS Statistics and Statdisk online to carry out hypothesis testing. The survey questionnaire will asking some opinions from respondents about the reason, effect, current solution and some alternation solution to overcome this issues. Throughout this research, the results show that most of the respondents are agreed to implement alternative solution such as drone, 3D printing and so on in construction industry to overcome skilled labour shortage.